Factors Influencing MCI Preparedness of Paramedic in XYZ Industrial City - Sulistyadi, Kohar; Ramli, Soehatman; Uddin, Saiful (ADI Journal on Recent Innovation, 2021)
Abstract Mass casualty incident (MCI) in industrial area is a definite threat that can result in environmental damage and loss of property and life. The causes of MCI can range from traffic accidents, industrial accidents, fires, toxic gases and terrorism. Paramedics, along with others emergency response team is among the first to reach at the incident scene to provide aid. Preparation is vital in ensuring that the response is fast, effective and efficient. The objective of the study is to analyze the relationship between knowledge, skills, attitudes and training on MCI Preparedness of paramedic in the XYZ Industrial city. Methodology of this paper is quantitative descriptive with cross sectional approach, while data analysis used the partial least square-structural equation model (PLS-SEM). 108 paramedics in XYZ industrial city involved and completed the survey. The research consist 5 latent variable models with 31 indicator variables. Data retrieval use a direct-share questionnaire. The result from data analysis revealed there is a positive and significant relationship between knowledge, skills, attitudes and training on MCI preparedness at t-value<1.96. Meanwhile, Skill has the most influence on MCI preparedness. Paramedics in the XYZ industrial city have the knowledge, skills, attitudes, training and preparedness that are in the "high category". Exogenous variables; knowledge, skills, attitudes and training explain 65.8% of the preparedness (endogenous variables). Continual commitment from paramedics and management is needed to maintain and enhance preparedness, knowledge, skills, attitudes and training in order to provide better medical emergency services. Keywords: PLS-SEM, MCI, preparedness, paramedics, industrial city.